Evaluating The Effect of Humidity on Adhesion Strength of Skin Adhesive - Arshad F. Jassem Al-Kaabi (Molecular and Cellular Biomedical Sciences, 2020)
Background: Skin adhesive has been used for attaching certain medical application to the human skin for functional and/or esthetic purposes. Silicone adhesive is the most common type of skin adhesives that are recently used. This study aims to evaluate the possible effect of humidity on the performance of silicone skin adhesive.Materials and Methods: Twenty-four silicone samples were divided into 2 main groups based on relative humidity (RH) exposure, namely 43% RH and 98% RH. Six samples from each group were tested for adhesion strength after 1 hour of adhesion, and the other 6 samples were tested after 2 hours of adhesion by conducting 180 degree peel test. The data were statistically analyzed for significant difference. Results: The results showed that at 43% RH, the adhesion strength was higher than the 98% RH group. The results also showed that at both humidity settings the adhesion strength after the first hours of adhesion was lower than the adhesion strength after the second hour.Conclusion: The silicone skin adhesive performance can be affected by the increase of relative humidity which needs more time of application to skin to reach the best adhesion function.Keywords: adhesions strength, humidity effect on adhesion, silicone adhesive, skin adhesives